Projeto e solução para o abastecimento de um grande consumidor: estudo de caso - SANTOS, Raquel Ferreira dos (2019)
The fact of the metropolitan region of Belém (RMB) come growing wildly in recent decades, in general, due to the exodus of rural populations, who comes in search of greater job opportunity and work together with a disorderly occupation of the medium, it became one major cause of contamination and degradation of surface and underground water ecosystems; since the lack of sanitation, irregular waste collection, combined with irregular housing, contribute to this picture. The physico-chemical and bacteriological analyzes for shallow wells existing in a capital club show that the water is not good for consumption. Nitrate parameter with concentrations between 16.0 to 25.0 are above the limit in all wells, classifying the water unfit for human consumption, as the limits considered by ordinance for nitrate is up to 10.0 mg / l N. bacteriological analysis of the wells also proved unsatisfactory, based on Ordinance No. 2914/2011 of the Ministry of Health. The construction of wells that capture water from deeper aquifers in this case Pirabas was based not only on the low degree of vulnerability, and great flow that such wells can reach, but they are also water excellent physical-chemical and bacteriological quality. The results of physicochemical analyzes of these wells show that in general the water is good for drinking. However the total iron parameter with concentrations of 0.5 and 0.7 mg / l concentrations exhibit at odds with the limits established by the Ministry of Health, which is a maximum of 0.3 mg / l.